Level of Knowledge on Hypertension and Associated Factors among Nursing Professionals of aSelected Tertiary Hospital in Bangladesh (IAHS Medical Journal, 2026)
Background: Hypertension is one of the major risk factors and a serious medical condition for cardiovascular diseases and can increase the risk of brain, kidney and other vital organs. Levels of knowledge about hypertension among the nurses might contribute effectively to prevent, treat and control the disease of patients. Thus, the objectives of this study were to identify the levels of knowledge about hypertensionamong nursing professionals of a selected tertiary hospital.Materials and methods: This cross-sectional study was conducted using the Hypertension Knowledge-Level Scale, which measures 6 dimensions of knowledge about hypertension (Definition, treatment, drug compliance, lifestyle, diet and complications).Results: There were 182 participants selected by convenience sampling method, among whom 42% nurses were with high knowledge on Hypertension, 28% had moderate knowledge and lastly 30% of them devoid of knowledge on Hypertension. This study revealed that, thelevel of knowledge on hypertension is strongly associated with sociodemographic status such as, Age (p